2017
DOI: 10.1590/2446-4740.06816
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and minimal detectable change of between-limb synchronization, weight-bearing symmetry, and amplitude of postural sway in individuals with stroke

Abstract: Introduction: Recently, variables related to between-limb synchronization of the centers of pressure (COP) have been proposed as measures of postural control in post-stroke patients. Although it is crucial in verifying their potential clinical use, the reliability of these variables is unknown. The aim of this work was to determine the reliability and minimal detectable change (MDC) of the peak of synchronization (ρ max ) in the anteroposterior (AP) and mediolateral (ML) directions, the time lag for the peak (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
8
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 29 publications
(59 reference statements)
7
8
2
Order By: Relevance
“…Nonetheless, we found no significant difference between the two populations. Our results confirm those of previous studies on stroke patients in which the side of the brain damaged was not considered [5,20]. As already mentioned, we found excellent reliability of WBA, although the interval between the two sessions was longer than that in the current literature (i.e.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Nonetheless, we found no significant difference between the two populations. Our results confirm those of previous studies on stroke patients in which the side of the brain damaged was not considered [5,20]. As already mentioned, we found excellent reliability of WBA, although the interval between the two sessions was longer than that in the current literature (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Given that the parameters of WBA and MLCOP are related [21], such results are not surprising. Although our results confirm those of Martello et al [5], they differ from those of other studies, which found weaker reliability for this parameter, likely due to various reasons, such as the stage of recovery (subacute versus chronic stroke) [4], the platform used (single versus double platform) [2], the longer duration (10s versus 30s) [4], and larger distance between the feet (3cm versus 14cm) [2]. Reliability of the APCOP measurement was also found to be excellent for LBD patients, whereas that of RBD patients was only moderate to poor.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations